Holistic integrated curriculum and its theoretical framework: implications for contemporary educational system - Embong, Rahimah; Hashim, Rosnani; Wan Yusoff, Wan Mazwati; Mohamad, Mohamad Zaidin (Medwell Publishing, 2015)
This study aims to propose a renewed concept of Holistic Integrated Curriculum (HIC) which will be helpful to avoid superficial and artificial integration of the curriculum. It will define the true concept of integrated curriculum from a holistic worldview, then to elucidate its theoretical framework and finally to discuss some implications of this concept for contemporary educational system. The issue of defining integrated curriculum has received a massive amount of attention from educational theorist and scholars from the West, since the turn of the 20th century. Initially, the integrated curriculum has been practiced by most contemporary educational institutions all around the world at all levels, i.e., primary, secondary and tertiary. However, there is a great diversity in their curricula, objectives and contents; hence their claims that their educational systems are fully and really integrated bring out more confusion. This leads to the discussion on revisiting the concept of HIC from a holistic worldview. The study makes it clear what is a theoretical framework that constructs this concept. This renewed concept has a flexible theoretical framework which is explained by 7 essential components and 7 integral elements. This theoretical framework is flexible and applicable to any contemporary educational institutions. Some implications of this renewed concept for contemporary educational system will be given in this study. The study utilizes the grounded theory which is a qualitative approach that generates theory from observation. In recent times is commonly used in the sociology of education parlance to link-up, the sporadic historical and philosophical data while proposing this concept. It is hoped that this conceptual study would lead to the reformulation of educational aims, the selection of curricular contents, as well as the application of pedagogical methods and mode of evaluation for contemporary educational institutions